The Legal Basis for Environmental Protection During Armed Conflicts - Raisah Mohammed Hassan Al-Shamrani; Ghufran Al-Qahtani (International Journal of Law Research and Studies, 2025)
This study examines the legal foundations of environmental protection during armed conflicts through the intersection of international humanitarian law, international environmental law, and international criminal law. The findings reveal that the existing framework—particularly the Geneva Conventions and their 1977 Additional Protocols, as well as the ENMOD, Basel, and Biodiversity Conventions, alongside the Rome Statute—provides an important normative basis, yet suffers from conceptual and procedural gaps. Chief among these is the ambiguity of the standard of “widespread, long-term, and severe damage,” the difficulty of proving causation, and the challenge of attributing violations to states or their agents in non-international armed conflicts. Principles such as military necessity, proportionality, distinction, and limitation of means, together with the principles of no harm, precaution, sustainability, and environmental equity, offer crucial guidance but remain limited in practical effectiveness due to weak monitoring tools, lack of scientific evidence protocols, and fragile chains of custody.The study highlights the close link between environmental protection, human dignity, and the right to sustainable development, emphasizing that environmental damage produces long-lasting health and economic consequences that undermine post-conflict recovery. The research concludes with actionable recommendations: the adoption of a binding international instrument that clearly defines “serious environmental damage” with measurable quantitative and qualitative criteria; the inclusion of grave environmental harm among “serious violations” of international humanitarian law, extending to non-international armed conflicts; and support for recognizing “ecocide” as an independent international crime with precise material and mental elements to reduce evidentiary burdens. The study further recommends establishing a specialized international monitoring mechanism relying on satellite imagery, laboratory analysis, and strict chain-of-custody protocols; harmonizing the Basel and Biodiversity Conventions with humanitarian relief efforts to prevent conflict zones from becoming toxic waste dumps; and integrating environmental recovery plans into peace agreements and reconstruction programs with compensation schemes tied to measurable environmental indicators. Finally, it emphasizes the need for military rules of engagement to incorporate precautionary and proportionality standards, with systematic training for both military and judicial actors to ensure the protection of high-risk facilities such as nuclear, chemical, and industrial sites.
Keywords: Environmental Protection; Armed Conflict; IHL; State Responsibility; No Harm Principle; Proportionality; ENMOD